India’s Strategic Conventional Weapon Systems: Implications on Strategic Stability in South Asia - Hina Shahid; Hassam Ahmed Siddique; Ummal Baneen, (ASIAN Journal of International Peace & Security (AJIPS), 2022)
India has been working on the modernization of its strategic and conventional weapon systems. So far, in terms of numbers, it holds a conventional ascendancy vis-à-vis Pakistan. India is investing in the various domains including space technologies, ballistic and cruise missiles and conventional weaponry. In the recent past, India has worked on multiple military deals with the US, Russia and France. More so, it has gone through doctrinal shifts that sum up the amount of research and development that has been invested in building up the Indian military might. Under the umbrella of CSD, India has plans for the amelioration of its conventional forces. In 2019, India became one of the four nations to possess an anti-satellite weapon. With Indian provocative measures under the CSD, Pakistan has been forced to respond back by shifting from Credible Minimum to Full-Spectrum Deterrence. Hence, strategic stability in South Asia is prevailing but with advanced strategic and conventional weapon systems, chance of a limited conflict escalating into an all-out war is a very likely scenario.